Paucity of data evaluating patient centred outcomes following sentinel lymph node dissection in endometrial cancer: A systematic review - Helena M. Obermair; Montana O'Hara; Andreas Obermair; Monika Janda (Elsevier, 2021)
Sentinel lymph node dissection (SLND) is presently used by the majority of gynaecologic oncologists for surgical staging of endometrial cancer. SLND assimilated into routine surgical practice because it increases precision of surgical staging and may reduce morbidity compared to a full, systematic LND. Previous research focussed on the accuracy of SLND. Patient centred outcomes have never been conclusively demonstrated. The objective of this systematic review was to evaluate patient centred outcomes of SLND for endometrial cancer patients. Literature published in the last five years (January 2015 to April 2020) was retrieved from PubMed, EMBASE, and Cochrane library, across five domains: (1) perioperative outcomes; (2) adjuvant treatment; (3) patient-reported outcomes (PROs); (4) lymphedema, and (5) cost. Covidence software ascertained a standardised and monitored review process. We identified 21 eligible studies. Included studies were highly heterogeneous, with widely varying outcome measures and reporting. SLND was associated with shorter operating times and lower estimated blood loss compared to systematic LND, but intra-operative and post-operative complications were not conclusively different. There was either no impact, or a trend towards less adjuvant treatment used in patients with SLND compared to systematic LND. SLND had lower prevalence rates of lymphedema compared to systematic LND, although this was shown only in three retrospective studies. Costs of surgical staging were lowest for no node sampling, followed by SLND, then LND. PROs were unable to be compared because of a lack of studies. The quality of evidence on patient-centred outcomes associated with SLND for surgical staging of endometrial cancer is poor, particularly in PROs, lymphedema and cost. The available studies were vulnerable to bias and confounding.Registration of Systematic Review: PROSPERO (CRD42020180339)